Transformation of Social Interaction in the Digital Era: A Literature Review on the Impact of Social Media on - Ika Rahma (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
The development of social media has changed the social interaction patterns of urban communities, causing a shift from face-to-face interactions to flexible, extensive, and sometimes fragmented digital interactions. This study uses a qualitative approach with a literature review method to analyze the impact of social media on social cohesion, focusing on the dynamics of interaction, sense of belonging, and solidarity in urban environments. The literature review highlights that social media can strengthen social networks, facilitate community mobilization, and build new social identities, but also has the potential to create pseudo-cohesion, digital segregation, and social polarization. The analysis shows that digital social cohesion depends on the intensity, depth, and space of interactions, and is influenced by cultural context, community norms, and urban heterogeneity. Research gaps are seen in understanding the resilience of digital cohesion, cross-generational interactions, and the integration of digital cohesion with traditional cohesion. This study concludes that the integration of classical sociological perspectives and contemporary digital communication is important for understanding the changing structure of urban social relations. The results of the study provide a conceptual foundation for further research and social interventions that can strengthen social networks in the digital era